In-plane experimental behavior of stone masonry walls under cyclic loading - Vasconcelos, Graça (2009)
Stone masonry is the oldest building material that survived until today, being used all over the world, particularly in impressive historic structures as an evidence of the achievements of ancient cultures. Stone walls are usually understood as structural elements able to withstand compression but they can also act as elements that provide resistance against in-plane wind and earthquake actions. Still, only a few experimental investigations are available in the literature, regarding the in-plane behavior of stone masonry walls under cyclic loading. The present work aims at obtaining a better insight on the behavior of stone masonry walls under cyclic in-plane loads. For this purpose, 23 walls were tested under different vertical normal stress level and different bond arrangement that represent typical walls typologies. The experimental results indicate these two factors play an important role on the in-plane behavior of stone masonry walls. In particular, ductility and energy dissipation depend significantly on the textural arrangement of the stones. It is also demonstrated that good quality stone masonry walls exhibit large nonlinear deformation capacity, with moderate damage levels. Finally, it is shown that the lateral resistance of stone walls provided by simplified analytical methods agrees reasonably well with the experimental results.